Dekonstruksi Ideologi Patriarki pada Cerita Rakyat “Gureongdeongdeong Sinseonbi” (구렁덩덩 신선비) - Yuliawati Dwi Widyaningrum (East Asian Review, 2026)
Traditionally, the Korean folktale “Gureongdeongdeong Sinseonbi” is viewed as promoting patriarchal ideology and female subservience during the Joseon era. This qualitative study, however, argues that the tale instead exposes the fragile foundations of patriarchy through internal contradictions that undermine male authority. Using Jacques Derrida’s deconstruction and Judith Butler’s theory of gender performativity, this research analyzes the power relations between male characters (Sinseonbi, Sinseonbi’s father, and Sinseonbi’s wife’s father) and female characters (Sinseonbi’s mother and wife). The findings demonstrate a reversal of binary oppositions, highlighted by dysfunctional male figures and women who assume masculine roles. The three male characters become passive subjects, lacking agency. They fail to demonstrate the ideal performance of masculinity, both as holders of supreme authority in various aspects of life and as a scholar. As a result, the female characters appropriate traditionally masculine roles, emerging as active subjects, problem solvers, and saviors. This research reveals the dependence of male authority on women, domestic instruments, and domestic space, showing that the patriarchal system collapses without women’s support. It also shows that women’s agency transcends the boundaries of femininity and masculinity as well as domestic and public spheres, reaffirming gender as a social construct rather than an innate trait